THE TECHNOLOGY OF LEATHER FILLING AND ITS IMPORTANCE - Abbosbek Muxtorov; Akmal Yusupovich Toshev; Tulkin Jumayevich Kodirov (Western European Studies, 2025)
This article provides a comprehensive analysis of leather filling technology, one of the key steps in the leather processing industry. Natural leather often contains surface irregularities and structural imperfections that negatively impact the final product’s aesthetics and durability. Filling involves applying special materials such as acrylic polymers, protein-based compounds, or synthetic latexes to smooth out the leather surface and improve physical-chemical properties. The study highlights the technological steps of surface preparation, application of fillers, drying, buffing, and finishing. The practical significance of filling in enhancing product quality, paint absorption, and market competitiveness is also emphasized. The article presents the types of fillers used in different industries and criteria for their selection based on usage context, ecological safety, and mechanical properties
Keywords: Leather processing; leather filling; filler materials